Training manual on Gracilaria culture and seaweed processing in China. (People's Republic of China Food and Agriculture Organization of the United Nations, United Nations Development Program, 1990)
Prepared for the GRACILARIA Culture and Seaweed Processing Training Course conducted by the Zhanjiang Fisheries College, Peoples Republic of China and organized by the Regional Seafarming Development and Demonstration Project
Keywords: Red algae; Gracilaria sp; Seaweed culture; Algal culture; Red algae culture